Knowledge and Awareness Regarding Radiation Safety among Radiology Study Program Students - Felayani, Fadli; Wibowo, Ardi Soesilo; Amin, Kholik Al (Jurnal EduHealth, 2023)
The increasing use of radiation in health services increases the risk to the public. The radiology study program as a producing institution has the challenge of ensuring that students fully understand and are aware of radiation safety. This study aims to determine the level of knowledge and awareness regarding radiation safety and related factors among radiology study program students.This was a quantitative study with a survey approach. The study instrument was a questionnaire that was delivered to 140 students from 7 radiology study programs in Indonesia consisting of 2 state institutions and 5 private institutions. The questionnaire consisted of 12 questions to evaluate knowledge regarding radiation safety, 16 questions to evaluate awareness regarding radiation safety and 6 questions to evaluate the learning experiences.Based on the study results on knowledge regarding radiation safety, 12.86% of respondents had "Poor" level of knowledge, 35.00% of respondents had "Moderate" level of knowledge, 20.71% of respondents had "Good" level of knowledge and 31.43% of respondents had "Very Good" level of knowledge. Respondents' radiation safety awareness in the "Poor" category was 3.57%, "Fair" 17.14%, "Good" 43.57% and the "Very Good" category 35.71%. Laboratory practical experience and the completeness of laboratory infrastructure had a positive effect on students' knowledge regarding radiation safety. Furthermore, clinical practice experience similarly had a positive effect on awareness regarding radiation safety. The study outcome can be applied as input for radiology study program educational institutions in developing learning to achieve competency regarding radiation safety.